The pragmatic aspect of the verbalized scenario “CONCEALING A MYSTERY”: strategies and tactics - Стрельченко, Ксенія Сергіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article investigates the inventory of strategies and tactics employed by the OWNER OF MYSTERY throughout the unfolding of the scenario “CONCEALING A MYSTERY”. The research material was selected from XX–XXI century English fiction. The analysis allowed us to single out the following strategies. The avoidance strategy is represented by the tactics of breaking off the conversation, changing the topic and ignoring the interlocutor. The strategy of refusing to provide the information inquired about can be realized explicitly and implicitly, in which case the corresponding tactics can be addressed to the OWNER OF MYSTERY (such as appealing to the inaccessibility of information, professional, social or moral norms, harm to the speaker as a result of divulging the information, the right to privacy, the positive image of the OWNER OF MYSTERY in the eyes of the QUESTOR, the physical or emotional state of the OWNER OF MYSTERY), the QUESTOR, the message, or the contact. The strategy of providing an answer violating the communicative maxims encompasses the tactics of violating the maxims of quality, quantity, relevance and manner.